WOMEN IN OLYMPICS - Dr. AJAZ AHMAD DAR; Prof. SUNIL KUMAR; GOWHAR AHMAD THOKAR; TANVEER ALI (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The adverse topic of women in sports stems from society's disregard to viewing women as persons. Women were, and in other parts of the world continue to be viewed as property of men and have no significant role in society. Being allowed into the Olympics was a step in the right direction for women across the world, but it was meager attempt equality. Women were still restricted by what events they were allowed to compete in, how they were trained and coached and even limited as to what they could wear. This article will evolve around the subject of female integration and participation in athletics in the Olympic Games, analyzing the initial difficulties they encountered, the role played by sports institutions as well as international federations and the Olympic International Committee.